Schaum's outlines probability, random variables, and random processes - Hsu, Hwei P. (Schaum's outline series, 2014)
With 405 fully-solved problems plus 23 problem-solving videos available online, this guide may be used with the following courses: Probability, Random Processes, Stochastic Processes, Probability and Random Variables, and Introduction to Probability and Statistics.-- Source other than Library of Congress.